2022
DOI: 10.1002/btm2.10475
|View full text |Cite
|
Sign up to set email alerts
|

The novel hyaluronic acid granular hydrogel attenuates osteoarthritis progression by inhibiting the TLR‐2/NF‐κB signaling pathway through suppressing cellular senescence

Abstract: In patients with mild osteoarthritis (OA), two to four monthly injections are required for 6 months due to the degradation of hyaluronic acid (HA) by peroxidative cleavage and hyaluronidase. However, frequent injections may lead to local infection and also cause inconvenience to patients during the COVID‐19 pandemic. Herein, we developed a novel HA granular hydrogel (n‐HA) with improved degradation resistance. The chemical structure, injectable capability, morphology, rheological properties, biodegradability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The destruction of periarticular bone and cartilage is a significant contributing element to OA, a prevalent chronic joint degenerative disease . It has been demonstrated that cellular senescence happens in OA chondrocytes and accelerates the development of OA. , Therefore, it is crucial to understand how cellular senescence-related genes in chondrocytes work in order to treat OA. Candidate biomarkers associated with cellular senescence can be found using bioinformatics techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The destruction of periarticular bone and cartilage is a significant contributing element to OA, a prevalent chronic joint degenerative disease . It has been demonstrated that cellular senescence happens in OA chondrocytes and accelerates the development of OA. , Therefore, it is crucial to understand how cellular senescence-related genes in chondrocytes work in order to treat OA. Candidate biomarkers associated with cellular senescence can be found using bioinformatics techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting the NF-κB pathway may alleviate OA [125]. Zhang et al attenuated OA progression by inhibiting the NF-κB pathway and suppressing chondrocyte senescence [126]. The aberrant activation of pathways, like JAK-STAT, MAPK, and Wnt, plays key roles in cell functions.…”
Section: Regulation Of Cell Signaling Pathwaysmentioning
confidence: 99%
“…It is reported that TLR2 can induce senescence in intervertebral disc cells, and o-vanillin may be a suitable drug for these patients (Mannarino et al 2021 ). Similarly, another study gives the novel hyaluronic acid granular hydrogel as a new strategy for osteoarthritis progression via suppressing TLR2-mediated cellular senescence (Zhang et al 2023 ). Furthermore, TLR3 causes senescence in patients infected with COVID-19 and tremendously increases SASP production (Tripathi et al 2021 ).…”
Section: Cell Senescencementioning
confidence: 99%